1999
DOI: 10.1016/s0014-5793(99)01022-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulation of Bacillus subtilis sigD by C‐terminal truncated LacR at translational level

Abstract: DegR is a positive regulator for degradative enzyme synthesis in Bacillus subtilis. The degR gene is transcribed by RNA polymerase containing c c D , and the level of its expression is low in a mecA-deficient mutant. In a search for suppressors of the mecA effect through mini-Tn10 transposon mutagenesis, a lacR mutation designated lacR288 was discovered. The B. subtilis lacR gene encodes the repressor for lacA which specifies L L-galactosidase, and therefore, inactivation of the lacR gene results in overproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…4). It encodes a transcriptional regulator that functions in the negative regulation of the b-galactosidase gene (lacA) as well as in the positive regulation of sigD in B. subtilis (Ogura et al 1999). Although a putative rho-independent transcription terminator is located downstream of the yvfI coding region (Kunst et al 1997), the lacR gene be function in regulating bacilysin activity and thus the observed loss of bacilysin production could actually be due to the polar effect of yvfI mutation on the downstream lacR gene.…”
Section: The Effect Of Yvfi and Lacr Null Mutations On The Bacilysin mentioning
confidence: 99%
“…4). It encodes a transcriptional regulator that functions in the negative regulation of the b-galactosidase gene (lacA) as well as in the positive regulation of sigD in B. subtilis (Ogura et al 1999). Although a putative rho-independent transcription terminator is located downstream of the yvfI coding region (Kunst et al 1997), the lacR gene be function in regulating bacilysin activity and thus the observed loss of bacilysin production could actually be due to the polar effect of yvfI mutation on the downstream lacR gene.…”
Section: The Effect Of Yvfi and Lacr Null Mutations On The Bacilysin mentioning
confidence: 99%
“…The two remaining isolates were tested to determine whether the ␤-galactosidase activity was derived from the yitJlacZ fusion rather than from expression of lacA, a cryptic ␤-galactosidase gene carried on the B. subtilis chromosome (26). The yitJ-lacZ fusion in these isolates was replaced with a neomycin resistance gene cassette by homologous recombination, and the resulting colonies were screened for lacZ expression.…”
Section: Vol 188 2006 B Subtilis Sam Synthetase Mutant 3675mentioning
confidence: 99%